Identifying the Valuation Effects and Agency Costs of Corporate Diversification: Evidence from the Geographic Diversification of U.S. Banks - Goetz, Martin R.; Laeven, Luc; Levine, Ross (Review of Financial Studies, 2013)
This paper assesses the impact of the geographic diversification of bank holding company (BHC) assets across the United States on their market valuations. Using two new identification strategies based on the dynamic process of interstate bank deregulation, we find that exogenous increases in geographic diversity reduced BHC valuations. We also find that the geographic diversification of BHC assets increased insider lending and reduced loan quality. Taken together, these findings are consistent with theories predicting that geographic diversity intensifies agency problems.